Detection of Psychotropic Compound in Coprophilous Fungi in District of Baturraden Banyumas Regency - Safira Amanda; Aris Mumpuni; Nuraeni Ekowati (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Coprophilous fungi or dung loving fungi are a group of fungi adapted to life on dung and fecal pellets of herbivorous animals. Coprophilous fungi contain psychotropic compounds. Psychotropics compounds are substances or drugs, both natural and synthetic, not narcotics, which have psychoactive properties through a selective influence on the central nervous system which causes distinctive changes in mental activity and behavior. Chemical Spot Test still remain an important tool for the preliminary identification of illicit drugs and other psychotropic compound in spite of developments in instrumental technology and the increased portability of this technology which enables its use in the field. Banyumas Regency is a very potential area as a habitat for coprophilous fungi, specifically in Baturraden District because there are many cattle farms where the dung is where the fungi grow, also the climate is suitable for fungal growth. make an inventory and identify the coprophilous fungi found in District of Baturraden Banyumas Regency and to detect the presence of psychotropic compound in the fungi. The research will be conducted using purposive random sampling and Color Test or Chemical Spot Test analysis. The obtained data is analyzed descriptively by comparing with Atlas of The Munsell Color System. This research obtained seven genera of coprophilous fungi i.e: Coprinellus sp., Coprinopsis sp., Entoloma sp., Gymnopus sp., Lepiota sp., Parasola sp. and Stropharia sp. that discovered in two cattle farms in Baturraden District.